Spectroscopic Characterization of GaAs and AlxGa1 – xAs / AlyGa1 – yAs Quantum Well Heterostructures - Mirgender Kumar; V.P. Singh (Журнал нано- та електронної фізики)
This work presents the results of the characterization of GaAs and AlxGa1 – xAs / AlyGa1 – yAs quantum well hetero-structures growth by MOVPE system. The main goal is to explore the ability of characterization techniques for multilayer structures like quantum wells. The characterization was performed using photoreflectance spectroscopy, surface photovoltaic spectroscopy and X-ray diffraction. The experimental results are verified by numerical simulation.